Stack and queue integrity on hostile platforms. - Devanbu, P.T (IEEE Transactions on software engineering)
When computationally intensive tasks have to be carried out on trusted, but limited platforms such as smart cards, it becomes necessary to compensate for the limited resources (memory, CPU speed) by off-loading implementations of data structures onto an available (but insecure, untrusted) fast coprocessor. However, data structures such as stacks, queues, RAMs, and hash tables can be corrupted (and made to behave incorrectly) by a potentially hostile implementation platform or by an adversary knowing or choosing data structure operations. The paper examines approaches that can detect violations of data structure invariants, while placing limited demands on the resources of the secure computing platform